Education policy and equal opportunity in Japan - Okada, Akito, 1967- (Asia-Pacific Studies: Past and Present., 2012)
In many societies today, educational aims or goals are commonly characterized in terms of "equality," "equal opportunity," "equal access" or "equal rights," the underlying assumption being that "equality" in some form is an intelligible and sensible educational ideal. Yet, there are different views and lively debates about what sort of equality should be pursued; in particular, the issue of equality of educational opportunity has served as justification for much of the postwar restructuring of educational systems around the world. The author explores different interpretations of the concept.